HUBUNGAN SELF-REGULATED LEARNING, MOTIVASI, KECERDASAN EMOSIONAL DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI AKADEMIK MAHASISWA PREKLINIK DAN KLINIK FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2022 - Cantika Salsabilla Onasis (2022)
Academic achievement is a learning outcome that reflects the efforts made in the education field. To predict student performance, academic achievement is used to identify competency levels and academic progress. Several factors influence increased academic achievement in this study; research was conducted on factors of self-regulated learning (SRL), motivation, emotional intelligence, and learning environment. The study aimed to determine the relationship between SRL, motivation, emotional intelligence, and learning environment on academic achievement of preclinical and clinical students at FK UPN Veterans Jakarta in 2022. This type of research was an analytical observational study with a cross- sectional design. The main instruments of this study were the MSLQ, WLEIS, and DREEM questionnaires. GPA measures academic achievement. The sample in the study was 249 consisting of 224 preclinical students and 25 clinical students. The sampling technique in this study was proportional stratified random sampling. Data were analysed by using the Spearman correlation test and the multiple linear regression backward method. The results of the correlation test showed a significant value between SRL and GPA in preclinical students (p=0.000) and clinical students (p=0.087); motivation with GPA of preclinical (p=0.000) and clinical students (p=0.011); emotional intelligence with GPA of preclinical (p=0.000) and clinical students (p=0.004); and the learning environment with GPA of preclinical (p=0.000) and clinical students (p=0.814). SRL, emotional intelligence, and learning environment influence the GPA of 49.5%. This study concludes that emotional intelligence is the variable that has the most significant influence on improving academic achievement.